Meckel-Gruber Syndrome: Clinical and Molecular Genetic Profiles in Two Fetuses and Review of the Current Literature - ARMAN, AHMET; GEÇKİNLİ, BİLGEN BİLGE; ALAVANDA, CEREN; EREN, ŞİRİN FUNDA (MARY ANN LIEBERT, INC, 2021)
Background: Meckel-Gruber syndrome (MKS; OMIM No. 249000) is a rare, in utero lethal disease characterized by occipital encephalocele, polycystic kidneys, and polydactyly. Methodology and Results: In this study, two fetuses diagnosed as having MKS in the prenatal period were evaluated on the basis of ultrasonographic findings, postmortem autopsy findings, and molecular genetic analyses. Using exome sequencing analyses a novel homozygous frameshift variant (NM_015631: c.530delA, p.Lys177Argfs*47) was detected at exon 4 of TCTN3 gene in case 1, and a novel homozygous synonymous variant (NM_025114: c.180G>A, p Lys60Lys) was detected at exon 3 of CEP290 gene in case 2. Case 1 is the first reported case in the literature, which showed the typical MKS clinical feature with a novel frameshift variation in the TCTN3 gene. The variant in case 2 is the first reported synonymous variant of CEP290 gene in the literature, which has been shown to affect splicing in a functional study at the RNA level. Conclusion: TCTN3 gene variants that were rarely associated with the typical MKS phenotype and all cases with these variations have been discussed in the context of genotype-phenotype. The detection of the first synonymous variant of CEP290 gene and the demonstration of its effect on splicing by a functional study are likely to contribute to the molecular etiology of MKS.
Keywords: TCTN3; exome sequencing; novel mutation; CEP290; Meckel-Gruber Syndrome; JOUBERT SYNDROME; MUTATIONS; CILIOGENESIS; CEP290